The Future of History: Cultural Heritage Tourism in Guangdong - Huang, Lu (Auckland University of Technology, 2006)
This thesis studies aspects of cultural heritage tourism in China. Relevant secondary tourism data in relation to tourist receipts and income generated from tourism activities are provided so as to present the different developmental state of the world and Chinese cultural heritage tourism. The thesis identifies that although many academic tourism researchers have discussed the cultural heritage issues, there is a gap that no English paper is available to identify the differences between current English and Chinese academic tourism studies in relation to cultural heritage issues. Cultural heritage issues studied by the current Chinese academic tourism researchers are limited to the World Heritage Sites inscribed by UNESCO, and local significant cultural heritage sites are left untouched. In this case, the English and Chinese literature in relation to cultural heritage, management and tourism product issues are reviewed and the gap that no English literature is available to discuss the different academic foci is filled. Secondly, a local cultural heritage site, Chen Ancestor's Temple, located in the southern part of China, is selected as the case study so as to challenge the current Chinese cultural heritage tourism study focus. A new direction which advocates the Chinese academic tourism researchers to turn their focus on local significant cultural heritage sites is established. To examine the current cultural heritage tourism in Chen Ancestor's Temple, two research methodologies are employed so as to gather first hand data. Quantitatively, a survey of tourist behaviors--before, during and after visitation of Chen Ancestor's Temple is conducted so as to supplement the statistics available and get to know more about Chen Ancestor's Temple current tourism development. Qualitatively, the in-depth interviews are conducted so as to investigate the issues of five stakeholder groups in relation to the development and management issues of Chen Ancestor's Temple. Themes are identified from the issues concerned by the five stakeholder groups and some recommendations are thus made.In all, this thesis compares the existing cultural heritage tourism literature in English and Chinese so as to advance the overall state of knowledge. The study of Chen Ancestor's Temple makes a further advance by establishing a new direction for Chinese academic tourism scholarship so as to focus towards locally significant cultural heritage sites.
Keywords: Cultural property; Tourism; Heritage tourism; China